A study on factors that influence the generation gaps among workers in Human Resources Department, Malaysia Airports Holding Berhad / Malek Mohamed Yatim and Haida Hanizah Ismail - Mohamed Yatim, Malek; Ismail, Haida Hanizah (Faculty of Business and Management, 2014)
Generations have been the subject of many different research projects and have been discussed frequently. The Baby Boomers tend to follow idols and think in group terms. Generation X is more individualistic and known as competitive generation. Generation Y is the global generation which connected to everyone and everything. There is an ongoing debate on the classification of generations. The influence and behavioral pattern towards work floor and management are also subject to debate. In order to make organization have effective and efficient in production, the right action might be taken to bridge the gaps before it is going to be large issues. The study has been conducted within Malaysia Airports Holding Berhad, involving 66 respondents in Department of Human Resources. Result of this study will be shown in the most influential factor that effect the multi – generation gaps among workers at Human Resources Department, Malaysia Airports Holding Berhad. It also shown the factors has significant relationship with the multi- generation gaps in that department. The recommendations for all objectives and future research also been discussed by researchers in this report.